Optimization of physical education and sports of students with disabilities throughout the entire period of study at the university - S.G. Adyrkhaev (Physical Education of Students)
Considered personal and proactive approach to physical education students with different nosologies and ensure close connection processes of personal training and physical development. In the experiment involved 644 students, with 2 and 3 of disability. The level of physical performance determined using the indexes. Identified organizational and methodological priorities of physical education and sports of students. Using the model of physical education allows full integration into the student environment. Students feel more comfortable. Students changing attitude toward themselves, manifested in the appropriate perception, finding camouflage disabilities struggle with her self-presentation. The effectiveness of didactic technology of physical education of students with disabilities in the pedagogical process.